Assessing the regional impact of Indonesian biomass burning emissions based on organic molecular tracers and chemical mass balance modeling - Engling, G.; He, Jun; Betha, R.; Balasubramanian, R. (Copernicus Publications, 2014)
Biomass burning activities commonly occur in Southeast Asia (SEA), and are particularly intense in Indonesia during the dry seasons. The effect of biomass smoke emissions on air quality in the city state of Singapore was investigated during a haze episode in October 2006. Substantially increased levels of airborne particulate matter (PM) and associated chemical species were observed during the haze period. Specifically, the enhancement in the concentration of molecular tracers for biomass combustion such as levoglucosan by as much as two orders of magnitude and the diagnostic ratios of individual organic compounds indicated that biomass burning emissions caused a regional smoke haze episode due to their long-range transport by prevailing winds. With the aid of air mass backward trajectories and chemical mass balance modeling, large-scale forest and peat fires in Sumatra and Kalimantan were identified as the sources of the smoke aerosol, exerting a significant impact on air quality in downwind areas, such as Singapore.